2006
DOI: 10.1088/0264-9381/23/17/016
|View full text |Cite
|
Sign up to set email alerts
|

The Poynting vector of stationary axisationary electrovac spacetimes reexamined

Abstract: Abstract. A simple formula, invariant under the duality rotation Φ → e iα Φ, is obtained for the Poynting vector within the framework of the Ernst formalism, and its application to the known exact solutions for a charged massive magnetic dipole is considered.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…The solution to the Einstein equations presented in this work is a static metric. This looks like to be in contradiction to previous results that state that in the spacetime associated to a static magnetic dipole in the presence of electric charges appears a frame-dragging effect [36,37], i.e. we have a stationary metric.…”
Section: Discussioncontrasting
confidence: 99%
“…The solution to the Einstein equations presented in this work is a static metric. This looks like to be in contradiction to previous results that state that in the spacetime associated to a static magnetic dipole in the presence of electric charges appears a frame-dragging effect [36,37], i.e. we have a stationary metric.…”
Section: Discussioncontrasting
confidence: 99%
“…Because of the axially symmetric character of the spacetime, only the component along the unitary vectorê φ survives [6]. In terms of the Ernst potentials [63] or more conveniently…”
Section: Vorticity Scalar and Poynting Vectormentioning
confidence: 99%
“…Surprisingly, if the astrophysical object does not rotate but possesses both electric and magnetic fields, the spacetime vorticity does not vanish [4][5][6]. In this case, frame dragging is of purely electromagnetic nature and it is associated with the existence of a nonvanishing electromagnetic Poynting vector around the source [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of any stationary energy flows created by the electric and magnetic charges in the binary dyonic configuration (2) can be easily established by analyzing the associated Poynting vector. In [11] it was demonstrated that the Poynting vector of a stationary axisymmetric electrovac spacetime can have only one non-zero component, and in [12] this ϕ-component was shown to be defined by the following simple formula:…”
Section: The Dyonic Emparan-teo Diholementioning
confidence: 99%